2015
DOI: 10.5223/pghn.2015.18.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Dedicated Breastfeeding Facility and Support Program for Exclusive Breastfeeding among Workers in Indonesia

Abstract: PurposeA mother's working environment is believed to be a major determinant of exclusive breastfeeding (EBF) practice. We aimed to define the influence of a facility dedicated to breastfeeding and a breastfeeding support program at the workplace on breastfeeding practice.MethodsA cross-sectional study was performed in five workplaces. The inclusion criteria were female workers whose last child was between 6 and 36 months old. Observational data were obtained and a questionnaire was filled out. The World Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 12 publications
3
44
0
7
Order By: Relevance
“…A set of self-administered questionnaires was distributed to obtain data related to demographic, occupational, knowledge, attitude and lactating practices in workplace. The questionnaire was modified from Basrowi et al study [6], after being consulted with experts from Division of…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A set of self-administered questionnaires was distributed to obtain data related to demographic, occupational, knowledge, attitude and lactating practices in workplace. The questionnaire was modified from Basrowi et al study [6], after being consulted with experts from Division of…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
“…5 Unfortunately, a study in Indonesia showed that only 21.5% of workers have access to proper lactation support at work and only 7.5% of workers benefits from adequate lactation education support/program provided by the employers, which was indicated the poor support of knowledge improvement initiatives in workers. 6 Hence, the prevalence of exclusive breastfeeding among bluecollar worker (manufacture labor) in Indonesia is only 19%, far below national prevalence which was 38%. 7 Workers were defined as white-collar workers by the following 14 job titles: administration, management, accounting, business, planning, personnel affairs, human resources, marketing, distribution, inspection, customer service, sales, supporting and international sales.…”
Section: Introductionmentioning
confidence: 96%
“…A similar study of Indonesian employed women had similar results. They were 2.7 times more likely to be exclusively breastfeeding at 6 months with a dedicated space for breastfeeding (Basrowi, Sulistomo, Adi, & Vandenplas, 2015). Research in the Unites States has also been conducted on specific barriers that minority populations, such as African-Americans or workers in low-wage jobs may experience around workplace support for breastfeeding (Johnson, Kirk, & Muzik, 2015).…”
Section: Workplace Policiesmentioning
confidence: 99%
“…Most of the studies reviewed were descriptive in design. Only three survey studies reported any association with potential for prediction when evaluating workplace policy (Basrowi et al, 2015;Kozhimannil et al, 2016;Tsai, 2013). All three studies reviewed found that women were twice as likely to breastfeed when there was a private space for lactation.…”
Section: Facilitators and Barriers For Employed Mothersmentioning
confidence: 99%
“…Furthermore, studies show that mothers will breast-feed their babies optimally when they receive appropriate information (3) and health workers' support (4) . A recent study found that knowledge, programme and facility support for breast-feeding mothers at the workplace in urban areas in Indonesia increased exclusive breast-feeding practices almost sixfold (5) . In contrast, information and promotional materials produced by breast-milk substitute companies (6) and the distribution of free samples of breast-milk substitutes have a detrimental impact on breast-feeding (7) .…”
mentioning
confidence: 99%